Belonging, Identity and Agency of EFL Instructors on Regional Campuses - Barrantes Elizondo, Lena (2023)
This article presents the results of research based on a life-history narrative research of the complexities involved in being a university teacher at a regional campus. Nine English as a Foreign Language (EFL) university instructors participated in this study. The data were analyzed and organized by following the three-dimensional, temporal-relational perspective on teacher agency offered by the ecological approach. Findings suggest that factors from the past that gave instructors a broad repertoire of responses to engage and act mainly included participants’ institutional and community belonging. Power differentials and the need for association and recognition stood out in participants’ stories.